ANALISIS VALIDITAS PENGEMBANGAN MEDIA PEMBELAJARAN POWER POINT INTERAKTIF PADA MATERI BANGUN DATAR KELAS IV SD/ MI - Ummu Khairiyah; Awaliah Dea Lestari (Universitas Islam Malang, 2022)
In learning there is still a lack of supporting media, students have difficulty understanding mathematics, because there is no concrete media, the teacher's lack of creativity in making learning media. Therefore, it is necessary to develop interactive power point learning media. The purpose of this study was to produce a product in the form of interactive power point media on valid grade IV SD/MI flat-building materials. This research is a research and development using the ADDIE model. The results showed that the feasibility of the material was 96.4%, the feasibility of language was 88.8%, and the feasibility of the media was 99.4% with very valid criteria. It can be concluded that the developed interactive power point media is valid to be applied to fourth grade students of SD/MI.